GAMBARAN PEMERIKSAAN INSPEKSI VISUAL ASETAT SEBAGAI DETEKSI LESI PRAKANKER SERVKS PADA WANITA PEKERJA SEKSUAL TIDAK LANGSUNG DI HOTSPOT X KECAMATAN LIMAPULUH PEKANBARU - Islami, Nursida; Fidiawati, Wiwit Ade; Sofian, Amru (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACKTCervical cancer wasthe second highest cancerin women in Indonesia. Indirect female sex workers had high risk for cervical cancer. World Health Organization (WHO) suggested screening to reduce the incidence of cervical cancer, alternative screening method which was relatively easy and often done in developing countries was Visual Inspection with Acetic Acid (VIA). This research was executed at hotspot X, Limapuluh district, Pekanbaru with the aim of describing the characteristics of respondents and to detect abnormal cervical epithelium using VIA. This research used descriptive research design, by using total sampling method there were 31 respondents. The result showed that 68% negative and 32% positive VIA. From the result of this study, it could be concluded that the majority of indirect female sexworkers (IFSW) had negative result of VIA, other wise IFSW who had positive result of VIA were suggested to get further examination.Keywords:Visual inspection with acetic acid, Cervical cancer, Indirect female sex workerPENDAHULUANKanker serviks merupakan keganasan pada serviks yang disebabkan oleh infeksi Human Papillomavirus khususnya tipe 16, 18, 31 dan 45.1,2 kanker ini menduduki peringkat keempatsebagai jenis kanker terseri